Analisis Penggunaan Media Pembelajaran Terhadap Motivasi Belajar PKN Siswa Kelas 1 SD - Salsabilla Salsabilla; Endina Dwiva Perbina Br Tarigan; Syahrial Syahrial (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze the use of learning media on the motivation to learn civics in grade 1 elementary school students. This research use desciptive qualitative approach. The subjects of this research were the homeroom teachers of class 1 of Attaufiq Elementary School in Medan and students of class 1 of Attaufiq Elementary School in Medan. Data collection techniques include observation and interviews. The results of the research show that students in class 1 of SD Attaufiq still have low learning motivation in civics subjects. The cause of the low learning motivation of grade 1 students at Attufiq Elementary School is due to the teacher's lack of ability to explain the material so that the learning process becomes monotonous and as a result students feel bored and bored during learning. Therefore, learning media is really needed to help students in the learning process with the existence of learning media. can help teachers clarify the meaning of the message they want to convey from a lesson theory so that it can motivate students to acquire certain knowledge and skills, and also with this learning media the teaching and learning process no longer seems monotonous.